Implementasi Kebijakan Pembangunan Perkotaan Dalam Pengembangan Wilayah Pusat Pemerintahan Daerah (Studi Kasus Pengembangan Wilayah Pusat Pemerintahan Daerah Melalui Pembangunan Ring Road Kota Madiun) - Sudibyo, Wulansari Puspa (Jurnal Administrasi Publik, 2015)
Abstraction: Policy Implementation of Urban Development in Regional Development Center of Local Government (Case Study of Regional Development, Local Government Center Building Through Ring Road Madiun City). The development problems that lack of focus so it needs policies to resolve development well. One of the government policy’s of urban development in the central region of the development of local government based on local spatial planning (RTRW). The purpose of this research is to determine how the implementation of the program and what are the inhibitor factors in the implementation of urban development policies in the development of the central area of local government. Research results showed that the implementation of urban development policy has been good. Based on Local Spatial Planning (RTRW) Madiun, Ring Road area that became the focus of research, development and the structure is already programmed on the agenda of local governments. Inhibitor factor in this development is the implementation of human resources policies, both in terms of human resources within the government and in terms of the surrounding community. Keywords: implementation of policy, Local Spatial Planning (RTRW), development of region Abstrak: Implementasi Kebijakan Pembangunan Perkotaan Dalam Pengembangan Wilayah Pusat Pemerintahan Daerah (Studi Kasus Pengembangan Wilayah Pusat Pemerintahan Daerah Melalui Pembangunan Ring Road Kota Madiun). Permasalahan pembangunan yang kurang fokus, perlu adanya kebijakan untuk membantu menyelesaikan pembangunan dengan baik. Salah satu kebijakan pemerintah melalui pembangunan perkotaan dalam pengembangan wilayah pusat pemerintahan daerah yang berdasarkan pada RTRW daerah. Tujuan penelitian ini adalah untuk mengetahui bagaimana implementasi program tersebut dan apa saja faktor penghambat dalam implementasi kebijakan pembangunan perkotaan dalam pengembangan wilayah pusat pemerintahan daerah. Hasil peneliti menujukkan bahwa implementasi kebijakan pembangunan perkotaan ini sudah baik. Berdasar pada RTRW Kota Madiun, kawasan Ring Road yang menjadi fokus peneliti, pembangunan sudah secara struktur dan terprogram pada agenda pemerintah daerah. Faktor penghambat pada implementasi kebijakan pembangunan ini adalah SDM, baik SDM dari segi pemerintah sendiri maupun dari segi masyarakat sekitar. Kata kunci: implementasi kebijakan, RTRW, pembangunan daerah